POLA PEMERTAHANAN BAHASA DALAM RANAH KELUARGA BERDASARKAN PERISTIWA BAHASA DAN KATEGORI GENDER - Tamrin Tamrin; Abdul Haliq (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Patterns of Language Retention in the Family Realm Based on Language Events and Gender Categories. This study aims to describe the form and pattern of Bugis language maintenance in Donggala Regency based on gender and the level of Bugis language maintenance between men and women in Donggala Regency. This study uses a sociolinguistic approach with questionnaire, interview, observation, and observation techniques. Furthermore, based on the analysis of the proportion of language defense patterns based on gender. The results of the analysis show that the pattern of language selection between men and women by the Bugis ethnicity in Donggala Regency is different. The pattern of using Bugis language by men is higher than the pattern of maintaining the use of Bugis language by women. The results showed that the level of maintenance of the male Bugis language was higher than the level of maintenance of the female Bugis language.